Fusarium and Neocosmospora Species Associated with Rot of Cactaceae and Other Succulent Plants - Sahar Kamali-Sarvestani; Reza Mostowfizadeh-Ghalamfarsa; Fatemeh Salmaninezhad; Santa Olga Cacciola (Journal of Fungi, 2022)
Infections by Fusarium and Fusarium-like species on cacti and other succulent plants cause the syndrome known as Fusarium dry rot and soft rot. There are only few records of Fusarium species as pathogens of cacti and other succulent plants from Iran. The objective of this study was the identification and characterization of fusarioid species recovered from ornamental succulents in Shiraz County, Iran. Three fusarioid species, including F. oxysporum, F. proliferatum, and Neocosmospora falciformis (formerly F. falciforme), were recovered from 29 diverse species of cacti and other succulents with symptoms of Fusarium dry rot and soft rot. The three fungal species were identified on the basis of morphological characters and the phylogenetic analysis of the translation elongation factor1-α (tef1) nuclear gene. The F. oxysporum isolates were identified as F. oxysporum f. sp. opuntiarum. The pathogenicity of the three fusarioid species was tested on a range of economically important ornamental succulents, mostly in the Cactaceae family. The three species showed a broad host spectrum and induced different types of symptoms on inoculated plants, including soft and dry rot, chlorosis, necrotic spots, wilt, drying, root and crown rot. This is the first report of N. falciformis as a pathogen of succulent plants worldwide.